Optimization of the Document Placement in the RFID Cabinet - Kiedrowicz Maciej (MATEC Web of Conferences, 2016)
The study is devoted to the issue of optimization of the document placement in a single RFID cabinet. It has been assumed that the optimization problem means the reduction of archivization time with respect to the information on all documents with RFID tags. Since the explicit form of the criterion function remains unknown, for the purpose of its approximation, the regression analysis method has been used. The method uses data from a computer simulation of the process of archiving data about documents. To solve the optimization problem, the modified gradient projection method has been used.